1995
DOI: 10.1021/ma00124a015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the "Strong" Polymer of n-Lauryl Methacrylate below and above the Glass Transition

Abstract: Dielectric spectroscopy (DS) and dynamic light scattering (DLS) are employed to study the dynamics of poly(«-lauryl methacrylate) (PnLMA) (Mw = 1.1 x 105) at temperatures below and above the glass transition temperature Tg (Tg 225 K). The DS and DLS data show no evidence for the splitting between the primary (a-) and secondary (/?-) relaxations within the experimental frequency range. The main process affecting DS and DLS is the mixed a/3-relaxation which bears similarities to a single a-process with regard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
3
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 9 publications
10
69
3
2
Order By: Relevance
“…3, were obtained for the activation energy of 27 kJ/mol. Distinct difference between theoretical and experimental value of T 1ρ at minimum may be due to temperature dependence of parameter describing distribution of correlation times and/or the increase in number of ethylene groups involved in the motion when temperature rises up, which was observed in other polymers [11,[16][17][18]. Motional behavior of the studied copolymer observed in NMR is reflected in dielectric and mechanical studies.…”
Section: Resultsmentioning
confidence: 78%
“…3, were obtained for the activation energy of 27 kJ/mol. Distinct difference between theoretical and experimental value of T 1ρ at minimum may be due to temperature dependence of parameter describing distribution of correlation times and/or the increase in number of ethylene groups involved in the motion when temperature rises up, which was observed in other polymers [11,[16][17][18]. Motional behavior of the studied copolymer observed in NMR is reflected in dielectric and mechanical studies.…”
Section: Resultsmentioning
confidence: 78%
“…that the changes in the osmotic modulus are the Figure 4a shows the relaxation rate for the cluster mode as a function of q 2 in the PLMA melt at 60ЊC illustrating its apparent diffusive character. At temperatures above about 5ЊC, the density fluctuations which formed the subject of the prior communication, 6 already lie outside of the experimental time window. Figure 4b shows the scattering vector dependence of the inverse scattered intensity, taken up with a low intensity laser and averaged over 30 min/run, for the cluster mode in the PLMA melt at 60ЊC, where the intensity of this mode has been obtained by apportioning the total intensity using the relative amplitude of the relevant mode.…”
Section: Cluster Modementioning
confidence: 95%
“…The first part of this work describes an invesponent as a function of PLMA concentration in the solutions and also a determination of the tigation of melt PLMA using dielectric spectroscopy and depolarized light scattering. 6 There it characteristic dimensions as a function of solvent content. was observed that the main process is a mixed ab-relaxation which could be studied over a broad temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated nanodomain size is compared with the size of dynamic heterogeneities estimated independently from calorimetric data for the polyethylene-like glass transition using the fluctuation approach. C = 10) was investigated by PCS and other methods [31,32] in order to compare the properties with those of the a process in the lower members. More recently, the development of the polyethylene-like glass transition (a PE ) with side-chain length was systematically investigated.…”
Section: Introductionmentioning
confidence: 99%